Deletional Alpha-Thalassemia Alleles in Amazon Blood Donors - Fernanda Cozendey Anselmo; Natália Santos Ferreira; Adolfo José da Mota; Marilda de Souza Gonçalves; Sérgio Roberto Lopes Albuquerque; Nelson Abrahim Fraiji; Ana Carla Dantas Ferreira; José Pereira de Moura Neto (Advances in Hematology)
Alpha-thalassemia is highly prevalent in the plural society of Brazil and is a public health problem. There is limited knowledge on its accurate frequency and distribution in the Amazon region. Knowing the frequency of thalassemia and the prevalence of responsible mutations is, therefore, an important step in the understanding and control program. Hematological and molecular data, in addition to serum iron and serum ferritin, from 989 unrelated first-time blood donors from Amazonas Hemotherapy and Hematology Foundation (FHEMOAM) were collected. In this study, the subjects were screened for −α3.7/4.2/20.5, −SEA, −FIL, and −MED deletions. Alpha-thalassemia screening was carried out between 2016 and 2017 among 714 (72.1%) male and 275 (27.9%) female donors. The aims of this analysis were to describe the distribution of various alpha-thalassemia alleles by gender, along with their genotypic interactions, and to illustrate the hematological changes associated with each phenotype. Amongst the patients, 5.35% (n = 53) were diagnosed with deletion –α−3.7 and only one donor with α−4.2 deletion. From the individuals with –α−3.7, 85.8% (n = 46) were heterozygous and 14.20% (n = 7) were homozygous. The frequency of the –α−3.7 deletion was higher in male (5.89%) than in female (4.0%). There is no significant difference in the distribution of –α−3.7 by gender (p=0.217). The –α20.5, −SEA, and −MED deletions were not found. All subjects were analyzed for serum iron and serum ferritin, with 1.04% being iron deficient (n = 5) and none with very high levels of stored iron (>220 µg/dL). Alpha-thalassemia-23.7kb deletion was the most common allele detected in Manaus blood donors, which is a consistent result, once it is the most common type of α-thalassemia found throughout the world. As expected, the mean of hematological data was significantly lower in alpha-thalassemia carriers (p<0.001), mainly homozygous genotype. Leukocytes and platelet count did not differ significantly. Due to the small number of individuals with iron deficiency found among blood donors, the differential diagnosis between the two types of anemia was not possible, even because minor changes were found among hematological parameters with iron deficiency and α-thalassemia. Despite this, the study showed the values of hematological parameters, especially MCV and MCH, are lower in donors with iron deficiency, especially when associated with α-thalassemia, and therefore, it may be useful to discriminate different types of microcytic anaemia. In conclusion, we believed screening for thalassemia trait should be included as part of a standard blood testing before blood donation. It should be noted that this was the first study to perform the screening for alpha deletions in blood donors from the Manaus region, and further studies are required to look at the effects of donated thalassemic blood.